2021
DOI: 10.1080/17474086.2021.1970522
|View full text |Cite
|
Sign up to set email alerts
|

Belantamab mafodotin for the treatment of relapsed/refractory multiple myeloma in heavily pretreated patients: a US cost-effectiveness analysis

Abstract: Background: Patients with relapsed/refractory multiple myeloma (RRMM) require several lines of therapy, with typically shorter remission duration with each additional line. Research design and methods:The cost-effectiveness of belantamab mafodotin (belamaf; DREAMM-2; NCT03525678) was compared with selinexor plus dexamethasone (SEL+DEX; STORM Part 2; NCT02336815) among patients with RRMM who have received at least four prior therapies. The base case used a US commercial payer's perspective over a 10-year time h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…We focused on the two CAR-T cell therapies vs belamaf as a recent study found that belamaf was lower cost with higher QALY gains relative to Selinexor. 12 In addition, our model allows for partitioning hypothetical patients based on response and we conducted several sensitivity checks.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on the two CAR-T cell therapies vs belamaf as a recent study found that belamaf was lower cost with higher QALY gains relative to Selinexor. 12 In addition, our model allows for partitioning hypothetical patients based on response and we conducted several sensitivity checks.…”
Section: Introductionmentioning
confidence: 99%